PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KENDARAAN BERMOTOR RODA EMPAT MENGGUNAKAN PEMROGRAMAN PHP DAN MySQL (Information Technology and Telematics, 2015)
Abstract Method of Analytic Hierarchy Process decision is drafting problem into a hierarchical structure so that decision makers can involve as much as possible all the factors that need to be considered and will be obvious link between factors with one another. With the existence of a decision support system decision will go smoothly with the best result in a decision, in this study the authors discuss a purchase decision in the four-wheeled vehicle in accordance with the new conditions predetermined selection criteria which includes the purchase price and the value of the car resale , fuel and car performance or specification which consists of a type of car, passenger capacity and transmission. The purpose of this system is perancangaan designing and making the electoral system to help facilitate the public in choosing the need for automobiles new condition in accordance with the type or types of vehicles in accordance with the selection criteria. This system development using HTML and PHP programming language with the MySQL database and the Apache web server as well as decision-making method using Analytic Hierarchy Process Keywords: decision support systems, cars, PHP, MySQL, AHP.